Global Cancer Transcriptome Quantifies Repeat Element Polarization between Immunotherapy Responsive and T Cell Suppressive Classes - Solovyov, Alexander; Vabret, Nicolas; Arora, Kshitij S.; Snyder, Alexandra; Funt, Samuel A.; Bajorin, Dean F.; Rosenberg, Jonathan E.; Bhardwaj, Nina; Ting, David T.; Greenbaum, Benjamin D. (Cell reports (Cambridge), 2018)
It has been posited that anti-tumoral innate activation is driven by derepression of endogenous repeats. We compared RNA sequencing protocols to assess repeat transcriptomes in The Cancer Genome Atlas (TCGA). Although poly(A) selection efficiently detects coding genes, most non-coding genes, and limited subsets of repeats, it fails to capture overall repeat expression and co-expression. Alternatively, total RNA expression reveals distinct repeat co-expression subgroups and delivers greater dynamic changes, implying they may serve as better biomarkers of clinical outcomes. We show that endogenous retrovirus expression predicts immunotherapy response better than conventional immune signatures in one cohort yet is not predictive in another. Moreover, we find that global repeat derepression, including the HSATII satellite repeat, correlates with an immunosuppressive phenotype in colorectal and pancreatic tumors and validate in situ. In conclusion, we stress the importance of analyzing the full spectrum of repeat transcription to decode their role in tumor immunity. [Display omitted] •RNA repeats are not properly detected in poly(A)-selected libraries•Expression of specific RNA repeat classes correlates with immune infiltrates in tumors•Quantifying nucleic acid repeats in tumors can serve as immunotherapy biomarkers Solovyov et al. compare protocols used in tumor transcriptional profiling. They show the most widely used poly(A) protocol fails to detect several classes of repeat RNAs. In contrast, repeat expression in total RNA sequencing can correlate with the cancer-immune phenotypes and patient responses to immunotherapy.